Edi-wow: An implementation of an online patient records management system for a dental clinic business - Rabe, Geraine Anne Zarene S. (Animo Repository, 2022)
This action research aimed at implementing an online patient record management system for a start-up dental clinic. In the two completed cycles, the team was able to optimize patient record management, migrated 350 patients’ records in an online system using the My Dental Clinic app, and integrated My Dental app to our process, which we call EDi-WOW or Enhanced Digital Ways of Working. The team used the 5S framework and People, Process, Technology framework as the team worked on the interventions. Cycle 1 focused on addressing the issue of long average process lead time of patient record management. During this cycle, the objective was to optimize patient record management. The team completed this cycle with success as the team was able to improve the average process lead time spent in managing the patient record management by 49%. In cycle 2, we focused on addressing the issue of the lack of a sustainable patient record management system. During this cycle the objective was to upgrade to an online patient record management system. The team completed this cycle with success as the team was able to migrate 350 patients' records to an online system, My Dental Clinic app. In the broader context, the research explored the people, process, and technology framework to show relationships among people, process, and technology, and the interrelationship of each component, such as effectiveness, technical competency, and efficiency, which would result in sustainability as supported by the EDi-WOW. This framework could be useful to small businesses that want to digitally enhance their ways of working. Keywords: patient record management, online patient record management system, enhanced digital ways of working, action research.